Polyester for UV viscosity-reducing glue as well as preparation method and application of polyester
By replacing traditional maleic anhydride with unsaturated monomers, an unsaturated polyester with carbon-carbon double bonds was prepared in the side chain, which solved the complex synthesis of existing UV adhesive-reducing glue and the residual glue, and achieved simple process and environmental protection. Efficient preparation of UV viscose reducing adhesive.
Patent Information
- Application Number
- CN202411764952.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-11
AI Technical Summary
The synthesis process of existing UV viscosity reducing glue is complicated, requiring multiple dissolution reactions and subsequent purification, and residual glue is likely to remain after UV irradiation.
Unsaturated monomers such as 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, etc. instead of traditional maleic anhydride, and UV detoxification glue is prepared through a simple process. Polyester, this polyester has high adhesion before light, and its adhesion drops sharply after light, and no residual glue remains.
It realizes the preparation of UV adhesive with simple process and environmental protection, with high reactivity and high toughness, and no residual glue after light, and is suitable for industrial bonding.
Smart Images

Figure BDA0005168678660000141 
Figure BDA0005168678660000151 
Figure BDA0005168678660000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to polyester for UV viscosity-reducing adhesives and a preparation method and application thereof. Background Art
[0002] UV photosensitive adhesive, also known as UV photo-strippable adhesive, maintains a high adhesive strength before ultraviolet irradiation, plays a role in fixing, supporting and protecting. When needed, the adhesive layer can be irradiated with ultraviolet light to quickly reduce its adhesion or lose its adhesion, and it is easy to peel off from the base material. Due to its special performance characteristics, the anti-viscosity adhesive has been widely used in many fields, such as precision electronic product processing, high-end glass protection, semiconductor wafer material grinding and cutting, product transportation and movement process protection, material recycling, etc. However, the existing anti-viscosity adhesive is often based on acrylates, compounded with multifunctional monomers and photoinitiators, and after UV irradiation, it is easy to leave residual adhesive on the device.
[0003] CN113736420A introduces terminal hydroxyitaconic acid-aliphatic diol copolyester into UV viscosity-reducing adhesive. The itaconic acid molecule contains two carboxyl groups and one double bond. The double bond on the side chain forms a conjugated relationship with the carboxyl group and has high reactivity. Under UV irradiation, the double bond undergoes a cross-linking reaction, reducing the 180° peel strength of the viscosity-reducing adhesive to 0.4N / 25mm. The viscosity-reducing effect is significant, and there is no residual adhesive or debonding. CN113698908A introduces terminal hydroxy fumaryl chloride-pentanediol copolyester into UV viscosity-reducing adhesive, improves the brittleness of the adhesive layer, and does not produce residual adhesive degumming after UV viscosity loss; At the same time, the terminal hydroxy fumaryl chloride-pentanediol copolyester has a higher double bond density on the main chain, so that the UV viscosity-reducing adhesive can have a higher crosslinking density without adding a multifunctional monomer, and the 180° peel strength before ultraviolet light can reach 19N / 25mm, and the adhesion performance is excellent. After ultraviolet light, the 180° peel strength can be as low as 0.4N / 25mm, which is easy to peel off, and the UV viscosity-reducing adhesive can complete the reaction within 1-3min under ultraviolet irradiation, and the reaction rate is fast and the conversion rate is high. However, the UV viscosity-reducing adhesive with non-acrylic acid as the main resin, its main resin such as terminal hydroxy itaconic acid-aliphatic diol copolyester, terminal hydroxy fumaryl chloride-pentanediol copolyester and other synthetic processes are relatively complicated, requiring multi-step dissolution reaction and subsequent purification.
[0004] Therefore, this field urgently needs a simple-process, environmentally friendly polyester for UV viscosity-reducing adhesive. The UV viscosity-reducing adhesive synthesized with this as the main body must have the characteristics of strong adhesion before light exposure and a sudden drop in adhesion after light exposure, and no residual adhesive remains on the device. Summary of the invention
[0005] Problem that the invention aims to solve
[0006] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a polyester for UV viscosity-reducing adhesive with simple process and environmental protection, and a UV viscosity-reducing adhesive synthesized with the polyester as the main body, which has strong bonding force before illumination, and the bonding force drops sharply after illumination, and no residual adhesive is produced.
[0007] Solutions for solving problems
[0008] The invention provides a polyester for UV viscosity-reducing adhesive. The raw materials for preparing the polyester for UV viscosity-reducing adhesive include a dibasic acid, a diol, and an unsaturated monomer. The unsaturated monomer is selected from one or more of 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, 1,2-epoxy-4-vinylcyclohexane, and 4-vinylbenzyl glycidyl ether.
[0009] Preferably, the dibasic acid comprises terephthalic acid, isophthalic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid, and dimer acid. More preferably, the dibasic acid is selected from one or more of terephthalic acid, isophthalic acid, adipic acid, sebacic acid, and dimer acid.
[0010] Preferably, the diol includes ethylene glycol, propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, pentanediol, 1,6-hexanediol, heptanediol, octanediol, nonanediol, decanediol, polyethylene glycol, more preferably, the diol is selected from one or more of ethylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,6-hexanediol.
[0011] Preferably, the amount of the unsaturated monomer is 50% to 70% of the amount of the dibasic acid in terms of molar ratio;
[0012] Preferably, the amount of the unsaturated monomer is 30% to 60% of the amount of the diol in terms of molar ratio.
[0013] Preferably, the hydroxyl value of the polyester for UV viscosity-reducing adhesive is 80 to 120 mg KOH / g;
[0014] More preferably, the hydroxyl value of the polyester for UV viscosity-reducing adhesive is 90-100 mg KOH / g.
[0015] Preferably, the raw material for preparing the polyester for UV viscosity-reducing adhesive further includes a catalyst;
[0016] More preferably, the catalyst is selected from one or more of tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, sodium acetate, zinc acetate, and magnesium acetate;
[0017] Further preferably, the catalyst is tetrabutyl titanate and / or sodium acetate.
[0018] The present invention also provides a method for preparing the polyester for UV viscosity-reducing adhesive, the method comprising the following steps:
[0019] (1) Under the protection of inert gas, the raw material is kept warm and then programmed to increase the temperature to carry out an esterification reaction;
[0020] (2) When the amount of by-products is greater than 90% of the theoretical value, the esterification reaction is terminated;
[0021] (3) After cooling, adding a heat stabilizer under the protection of an inert gas, heating and polycondensing to obtain the polyester for UV viscosity-reducing adhesive.
[0022] Preferably, the inert gas in step (1) is nitrogen;
[0023] Preferably, the temperature of the insulation in step (1) is 100° C. to 120° C., and more preferably, the temperature of the insulation in step (1) is 100° C.;
[0024] Preferably, the insulation time in step (1) is 40 to 80 minutes, and more preferably, the insulation time in step (1) is 60 minutes;
[0025] Preferably, the programmed temperature increase in step (1) is to increase the temperature to 220°C to 240°C, and more preferably, the programmed temperature increase in step (1) is to increase the temperature to 230°C;
[0026] Preferably, the rate of the programmed temperature increase in step (1) is 0.5 to 2°C / min, more preferably, the rate of the programmed temperature increase in step (1) is 1°C / min;
[0027] Preferably, the cooling in step (3) is to 180°C to 200°C, and more preferably, the cooling in step (3) is to 190°C;
[0028] Preferably, the inert gas in step (3) is nitrogen;
[0029] Preferably, the heat stabilizer in step (3) is selected from one or more of dimethyl phosphate, trimethyl phosphate, triphenyl phosphate, and triphenyl phosphite. More preferably, the heat stabilizer in step (3) is trimethyl phosphate.
[0030] Preferably, the temperature in step (3) is raised to 200°C to 240°C, and more preferably, the temperature in step (3) is raised to 230°C;
[0031] Preferably, the polycondensation in step (3) is performed until the hydroxyl value of the product is 80 to 120 mg KOH / g.
[0032] The present invention also provides a UV viscosity-reducing adhesive, wherein the raw materials for preparing the UV viscosity-reducing adhesive include the polyester for the UV viscosity-reducing adhesive;
[0033] Preferably, the raw materials for preparing the UV viscosity-reducing adhesive further include diisocyanate, diol, acrylate, reactive copolyester and photoinitiator.
[0034] The present invention also provides a UV anti-viscosity tape, which comprises a base film, the UV anti-viscosity adhesive, and a release film;
[0035] Preferably, the thickness of the UV adhesive tape is 5 to 20 μm, more preferably, the thickness of the UV adhesive tape is 10 μm;
[0036] Preferably, the base film is a PET film.
[0037] The present invention also provides an application of the polyester for UV viscosity-reducing adhesive, the UV viscosity-reducing adhesive, or the UV viscosity-reducing tape in the field of industrial bonding.
[0038] Effects of the Invention
[0039] The polyester for UV viscosity-reducing adhesive of the present invention uses unsaturated monomers to replace traditional maleic anhydride (MA), introduces unsaturated carbon-carbon double bonds into the side chains of the polyester structure, and the prepared polyester for UV viscosity-reducing adhesive is an unsaturated polyester with carbon-carbon double bonds in the side chains, has no carbon-carbon double bonds on the main chain, and all carbon-carbon double bonds are in the side chains, and has high toughness and high reaction activity.
[0040] The unsaturated monomer used in the present invention does not contain an ester bond, and will not undergo hydrolysis or alcoholysis during the reaction. A one-step reaction can be used, and the reaction is easy to control and is not prone to cross-linking.
[0041] The UV viscosity-reducing adhesive prepared by using the polyester for UV viscosity-reducing adhesive of the present invention has good adhesion to the PET film, and after UV irradiation, the adhesion value is significantly reduced without residual adhesive. DETAILED DESCRIPTION
[0042] In order to make the technical solutions and beneficial effects of the present invention more clearly understood, the following is a detailed description by listing specific embodiments. Unless otherwise defined, the technical and scientific terms used herein have the same meanings as those in the technical field to which this application belongs.
[0043] The invention provides a polyester for UV viscosity-reducing adhesive. The raw materials for preparing the polyester for UV viscosity-reducing adhesive include a dibasic acid, a diol, and an unsaturated monomer. The unsaturated monomer is selected from one or more of 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, 1,2-epoxy-4-vinylcyclohexane, and 4-vinylbenzyl glycidyl ether.
[0044] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, 1,2-epoxy-4-vinylcyclohexane, or 4-vinylbenzyl glycidyl ether.
[0045] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, or 1,2-epoxy-4-vinylcyclohexane.
[0046] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, or 4-vinylbenzyl glycidyl ether.
[0047] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, 1,2-epoxy-4-vinylcyclohexane, or 4-vinylbenzyl glycidyl ether.
[0048] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-9-decene, 1,2-epoxy-4-vinylcyclohexane, or 4-vinylbenzyl glycidyl ether.
[0049] In certain embodiments, the unsaturated monomer is 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, 1,2-epoxy-4-vinylcyclohexane, or 4-vinylbenzyl glycidyl ether.
[0050] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, or 1,2-epoxy-9-decene.
[0051] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, or 1,2-epoxy-4-vinylcyclohexane.
[0052] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, or 4-vinylbenzyl glycidyl ether.
[0053] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-9-decene, or 1,2-epoxy-4-vinylcyclohexane.
[0054] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-9-decene, or 4-vinylbenzyl glycidyl ether.
[0055] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene, 1,2-epoxy-4-vinylcyclohexane, or 4-vinylbenzyl glycidyl ether.
[0056] In certain embodiments, the unsaturated monomer is 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, or 1,2-epoxy-4-vinylcyclohexane.
[0057] In certain embodiments, the unsaturated monomer is 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, or 4-vinylbenzyl glycidyl ether.
[0058] In certain embodiments, the unsaturated monomer is 1,2-epoxy-7-octene, 1,2-epoxy-4-vinylcyclohexane, or 4-vinylbenzyl glycidyl ether.
[0059] In certain embodiments, the unsaturated monomer is 1,2-epoxy-9-decene, 1,2-epoxy-4-vinylcyclohexane, or 4-vinylbenzyl glycidyl ether.
[0060] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene or 1,2-epoxy-7-octene.
[0061] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene or 1,2-epoxy-9-decene.
[0062] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene or 1,2-epoxy-9-decene.
[0063] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene or 4-vinylbenzyl glycidyl ether.
[0064] In certain embodiments, the unsaturated monomer is 1,2-epoxy-7-octene or 1,2-epoxy-7-octene.
[0065] In certain embodiments, the unsaturated monomer is 1,2-epoxy-7-octene or 1,2-epoxy-4-vinylcyclohexane.
[0066] In certain embodiments, the unsaturated monomer is 1,2-epoxy-7-octene or 4-vinylbenzyl glycidyl ether.
[0067] In certain embodiments, the unsaturated monomer is 1,2-epoxy-9-decene or 1,2-epoxy-4-vinylcyclohexane.
[0068] In certain embodiments, the unsaturated monomer is 1,2-epoxy-9-decene or 4-vinylbenzyl glycidyl ether.
[0069] In certain embodiments, the unsaturated monomer is 1,2-epoxy-4-vinylcyclohexane or 4-vinylbenzyl glycidyl ether.
[0070] In certain embodiments, the unsaturated monomer is 1,2-epoxy-5-hexene.
[0071] In certain embodiments, the unsaturated monomer is 1,2-epoxy-7-octene.
[0072] In certain embodiments, the unsaturated monomer is 1,2-epoxy-9-decene.
[0073] In certain embodiments, the unsaturated monomer is 1,2-epoxy-4-vinylcyclohexane.
[0074] In certain embodiments, the unsaturated monomer is 4-vinylbenzyl glycidyl ether.
[0075] In certain embodiments, the dibasic acid comprises terephthalic acid, isophthalic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid, and dimer acid.
[0076] In certain embodiments, the dibasic acid is selected from one or more of terephthalic acid, isophthalic acid, adipic acid, sebacic acid, and dimer acid.
[0077] In certain embodiments, the dibasic acid is terephthalic acid, isophthalic acid, adipic acid, sebacic acid, or dimer acid.
[0078] In certain embodiments, the dibasic acid is terephthalic acid, isophthalic acid, adipic acid, or sebacic acid.
[0079] In certain embodiments, the dibasic acid is terephthalic acid, isophthalic acid, adipic acid, or dimer acid.
[0080] In certain embodiments, the dibasic acid is terephthalic acid, isophthalic acid, sebacic acid, or dimer acid.
[0081] In certain embodiments, the dibasic acid is terephthalic acid, adipic acid, sebacic acid, or dimer acid.
[0082] In certain embodiments, the dibasic acid is isophthalic acid, adipic acid, sebacic acid, or dimer acid.
[0083] In certain embodiments, the dibasic acid is terephthalic acid, isophthalic acid, or adipic acid.
[0084] In certain embodiments, the dibasic acid is terephthalic acid, isophthalic acid, or sebacic acid.
[0085] In certain embodiments, the diacid is terephthalic acid, isophthalic acid, or dimer acid.
[0086] In certain embodiments, the dibasic acid is terephthalic acid, adipic acid, or sebacic acid.
[0087] In certain embodiments, the diacid is terephthalic acid, adipic acid, or dimer acid.
[0088] In certain embodiments, the dibasic acid is terephthalic acid, sebacic acid, or dimer acid.
[0089] In certain embodiments, the dibasic acid is isophthalic acid, adipic acid, or sebacic acid.
[0090] In certain embodiments, the dibasic acid is isophthalic acid, adipic acid, or dimer acid.
[0091] In certain embodiments, the dibasic acid is adipic acid, sebacic acid, or dimer acid.
[0092] In certain embodiments, the dibasic acid is terephthalic acid or isophthalic acid.
[0093] In certain embodiments, the dibasic acid is terephthalic acid or adipic acid.
[0094] In certain embodiments, the dibasic acid is terephthalic acid or sebacic acid.
[0095] In certain embodiments, the diacid is terephthalic acid or dimer acid.
[0096] In certain embodiments, the dibasic acid is isophthalic acid or adipic acid.
[0097] In certain embodiments, the dibasic acid is isophthalic acid or sebacic acid.
[0098] In certain embodiments, the dibasic acid is isophthalic acid or dimer acid.
[0099] In certain embodiments, the dibasic acid is adipic acid or sebacic acid.
[0100] In certain embodiments, the dibasic acid is adipic acid or dimer acid.
[0101] In certain embodiments, the dibasic acid is sebacic acid or dimer acid.
[0102] In certain embodiments, the diacid is terephthalic acid.
[0103] In certain embodiments, the diacid is isophthalic acid.
[0104] In certain embodiments, the diacid is adipic acid.
[0105] In certain embodiments, the dibasic acid is sebacic acid.
[0106] In certain embodiments, the diacid is a dimer acid.
[0107] In certain embodiments, the diol includes ethylene glycol, propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, pentanediol, 1,6-hexanediol, heptanediol, octanediol, nonanediol, decanediol, and polyethylene glycol.
[0108] In certain embodiments, the diol is selected from one or more of ethylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, and 1,6-hexanediol.
[0109] In certain embodiments, the diol is ethylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, or 1,6-hexanediol.
[0110] In certain embodiments, the diol is ethylene glycol, 1,4-butanediol, or 2-methyl-1,3-propanediol.
[0111] In certain embodiments, the diol is ethylene glycol, 1,4-butanediol, or 1,6-hexanediol.
[0112] In certain embodiments, the diol is ethylene glycol, 2-methyl-1,3-propanediol, or 1,6-hexanediol.
[0113] In certain embodiments, the diol is 1,4-butanediol, 2-methyl-1,3-propanediol, or 1,6-hexanediol.
[0114] In certain embodiments, the diol is ethylene glycol or 1,4-butanediol.
[0115] In certain embodiments, the diol is ethylene glycol or 2-methyl-1,3-propanediol.
[0116] In certain embodiments, the diol is ethylene glycol or 1,6-hexanediol.
[0117] In certain embodiments, the diol is 1,4-butanediol or 2-methyl-1,3-propanediol.
[0118] In certain embodiments, the diol is 1,4-butanediol or 1,6-hexanediol.
[0119] In certain embodiments, the diol is 2-methyl-1,3-propanediol or 1,6-hexanediol.
[0120] In certain embodiments, the diol is ethylene glycol.
[0121] In certain embodiments, the diol is 1,4-butanediol.
[0122] In certain embodiments, the diol is 2-methyl-1,3-propanediol.
[0123] In certain embodiments, the diol is 1,6-hexanediol.
[0124] In certain embodiments, the amount of the unsaturated monomer is 50% to 70% of the amount of the dibasic acid in terms of molar ratio.
[0125] In certain embodiments, the amount of the unsaturated monomer is 50%, or 50.5%, or 51%, or 51.5%, or 52%, or 52.5%, or 53%, or 53.5%, or 54%, or 54.5%, or 55%, or 55.5%, or 56%, or 56.5%, or 57%, or 57.5%, or 58%, or 58.5% of the amount of the dibasic acid. %, or 59%, or 59.5%, or 60%, or 60.5%, or 61%, or 61.5%, or 62%, or 62.5%, or 63%, or 63.5%, or 64%, or 64.5%, or 65%, or 65.5%, or 66%, or 66.5%, or 67%, or 67.5%, or 68%, or 68.5%, or 69%, or 69.5%, or 70%.
[0126] In certain embodiments, the amount of the unsaturated monomer is 30% to 60% of the amount of the diol, based on molar ratio.
[0127] In certain embodiments, the amount of the unsaturated monomer is 30%, or 31%, or 32%, or 33%, or 34%, or 35%, or 36%, or 37%, or 38%, or 39%, or 40%, or 41%, or 42%, or 43%, or 44%, or 45%, or 46%, or 47%, or 48%, or 49%, or 50%, or 51%, or 52%, or 53%, or 54%, or 55%, or 56%, or 57%, or 58%, or 59%, or 60% of the amount of the diol, based on a molar ratio.
[0128] In certain embodiments, the polyester for UV viscosity-reducing adhesive has a hydroxyl value of 80 to 120 mg KOH / g.
[0129] In certain embodiments, the hydroxyl value of the UV viscosity reducing polyester is 80 mg KOH / g, or 81 mg KOH / g, or 82 mg KOH / g, or 83 mg KOH / g, or 84 mg KOH / g, or 85 mg KOH / g, or 86 mg KOH / g, or 87 mg KOH / g, or 88 mg KOH / g, or 89 mg KOH / g, or 90 mg KOH / g, or 91 mg KOH / g, or 92 mg KOH / g, or 93 mg KOH / g, or 94 mg KOH / g, or 95 mg KOH / g, or 96 mg KOH / g, or 97 mg KOH / g, or 98 mg KOH / g, or 99 mg KOH / g, or 100 mg KOH / g, or 101 mg KOH / g, or 102 mg KOH / g, or 103 mg KOH / g, or 104 mg or 114 mg KOH / g, or 115 mg KOH / g, or 116 mg KOH / g, or 117 mg KOH / g, or 118 mg KOH / g, or 119 mg KOH / g, or 120 mg KOH / g.
[0130] In certain embodiments, the hydroxyl value of the polyester for UV viscosity-reducing adhesive is 90 to 100 mg KOH / g.
[0131] In certain embodiments, the raw material for preparing the polyester for UV viscosity-reducing adhesive further includes a catalyst.
[0132] In certain embodiments, the catalyst is selected from one or more of tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, sodium acetate, zinc acetate, and magnesium acetate.
[0133] In certain embodiments, the catalyst is tetrabutyl titanate and / or sodium acetate.
[0134] In certain embodiments, the catalyst is tetrabutyl titanate and sodium acetate.
[0135] In certain embodiments, the catalyst is tetrabutyl titanate.
[0136] In certain embodiments, the catalyst is sodium acetate.
[0137] The present invention also provides a method for preparing the polyester for UV viscosity-reducing adhesive, the method comprising the following steps:
[0138] (1) Under the protection of inert gas, the raw material is kept warm and then programmed to increase the temperature to carry out an esterification reaction;
[0139] (2) When the amount of by-products is greater than 90% of the theoretical value, the esterification reaction is terminated;
[0140] (3) After cooling, adding a heat stabilizer under the protection of an inert gas, heating and polycondensing to obtain the polyester for UV viscosity-reducing adhesive.
[0141] In certain embodiments, the inert gas in step (1) is nitrogen.
[0142] In certain embodiments, the insulation temperature in step (1) is 100°C to 120°C.
[0143] In certain embodiments, the insulation temperature in step (1) is 100°C, or 101°C, or 102°C, or 103°C, or 104°C, or 105°C, or 106°C, or 107°C, or 108°C, or 109°C, or 110°C, or 111°C, or 112°C, or 113°C, or 114°C, or 115°C, or 116°C, or 117°C, or 118°C, or 119°C, or 120°C.
[0144] In certain embodiments, the insulation temperature in step (1) is 100°C.
[0145] In certain embodiments, the insulation time in step (1) is 40 to 80 minutes.
[0146] In certain embodiments, the insulation time of step (1) is 40min, or 41min, or 42min, or 43min, or 44min, or 45min, or 46min, or 47min, or 48min, or 49min, or 50min, or 51min, or 52min, or 53min, or 54min, or 55min, or 56min, or 57min, or 58min, or 59min, or 60min, or 61min, or 62min, or 63min, or 64min, or 65min, or 66min, or 67min, or 68min, or 69min, or 70min, or 71min, or 72min, or 73min, or 74min, or 75min, or 76min, or 77min, or 78min, or 79min, or 80min.
[0147] In certain embodiments, the insulation time in step (1) is 60 minutes.
[0148] In certain embodiments, the programmed temperature increase in step (1) is to increase the temperature to 220°C to 240°C.
[0149] In certain embodiments, the programmed temperature increase in step (1) is to 220°C, or 221°C, or 222°C, or 223°C, or 224°C, or 225°C, or 226°C, or 227°C, or 228°C, or 229°C, or 230°C, or 231°C, or 232°C, or 233°C, or 234°C, or 235°C, or 236°C, or 237°C, or 238°C, or 239°C, or 240°C.
[0150] In certain embodiments, the programmed temperature increase in step (1) is to increase the temperature to 230°C.
[0151] In certain embodiments, the rate of the programmed temperature increase in step (1) is 0.5-2°C / min.
[0152] In certain embodiments, the rate of the programmed temperature increase in step (1) is 0.5°C / min, or 0.6°C / min, or 0.7°C / min, or 0.8°C / min, or 0.9°C / min, or 1°C / min, or 1.1°C / min, or 1.2°C / min, or 1.3°C / min, or 1.4°C / min, or 1.5°C / min, or 1.6°C / min, or 1.7°C / min, or 1.8°C / min, or 1.9°C / min, or 2°C / min.
[0153] In certain embodiments, the rate of the programmed temperature increase in step (1) is 1°C / min.
[0154] In certain embodiments, the amount of by-products in step (2) is greater than 90% of the theoretical value when the esterification rate is greater than 90% and the acid value of the system is less than 10.
[0155] In certain embodiments, the cooling in step (3) is to a temperature of 180°C to 200°C.
[0156] In certain embodiments, the cooling in step (3) is cooling to 180°C, or 181°C, or 182°C, or 183°C, or 184°C, or 185°C, or 186°C, or 187°C, or 188°C, or 189°C, or 190°C, or 191°C, or 192°C, or 193°C, or 194°C, or 195°C, or 196°C, or 197°C, or 198°C, or 199°C, or 200°C.
[0157] In certain embodiments, the cooling in step (3) is cooling to 190°C.
[0158] In certain embodiments, the inert gas in step (3) is nitrogen.
[0159] In certain embodiments, the thermal stabilizer in step (3) is selected from one or more of dimethyl phosphate, trimethyl phosphate, triphenyl phosphate, and triphenyl phosphite.
[0160] In certain embodiments, the thermal stabilizer in step (3) is trimethyl phosphate.
[0161] In certain embodiments, the heating in step (3) is to a temperature of 200°C to 240°C.
[0162] In certain embodiments, the temperature in step (3) is increased to 200°C, or 201°C, or 202°C, or 203°C, or 204°C, or 205°C, or 206°C, or 207°C, or 208°C, or 209°C, or 210°C, or 211°C, or 212°C, or 213°C, or 214°C, or 215°C, or 216°C, or 217°C, or 218°C. ℃, or 219℃, or 220℃, or 221℃, or 222℃, or 223℃, or 224℃, or 225℃, or 226℃, or 227℃, or 228℃, or 229℃, or 230℃, or 231℃, or 232℃, or 233℃, or 234℃, or 235℃, or 236℃, or 237℃, or 238℃, or 239℃, or 240℃.
[0163] In certain embodiments, the heating in step (3) is to 230°C.
[0164] In certain embodiments, the polycondensation in step (3) is performed until the hydroxyl value of the product is 80 to 120 mg KOH / g.
[0165] In certain embodiments, the polycondensation in step (3) is polycondensation until the hydroxyl value of the product is 80 mg KOH / g, or 81 mg KOH / g, or 82 mg KOH / g, or 83 mg KOH / g, or 84 mg KOH / g, or 85 mg KOH / g, or 86 mg KOH / g, or 87 mg KOH / g, or 88 mg KOH / g, or 89 mg KOH / g, or 90 mg KOH / g, or 91 mg KOH / g, or 92 mg KOH / g, or 93 mg KOH / g, or 94 mg KOH / g, or 95 mg KOH / g, or 96 mg KOH / g, or 97 mg KOH / g, or 98 mg KOH / g, or 99 mg KOH / g, or 100 mg KOH / g, or 101 mg KOH / g, or 102 mg KOH / g, or 103 mg KOH / g, or 104 mg or 114 mg KOH / g, or 115 mg KOH / g, or 116 mg KOH / g, or 117 mg KOH / g, or 118 mg KOH / g, or 119 mg KOH / g, or 120 mg KOH / g.
[0166] The present invention also provides a UV viscosity-reducing adhesive. The raw materials for preparing the UV viscosity-reducing adhesive include the polyester for the UV viscosity-reducing adhesive.
[0167] In certain embodiments, the raw materials for preparing the UV viscosity-reducing adhesive further include diisocyanate, diol, acrylate, reactive copolyester and photoinitiator.
[0168] In certain embodiments, the diisocyanate is selected from one or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and L-lysine diisocyanate.
[0169] In certain embodiments, the diisocyanate is isophorone diisocyanate.
[0170] In certain embodiments, the diol is selected from one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, pentanediol, 1,6-hexanediol, heptanediol, octanediol, nonanediol, decanediol, and polyethylene glycol.
[0171] In certain embodiments, the diol is 1,4-butanediol.
[0172] In certain embodiments, the acrylate is selected from one or more of diethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,3-butanediol dimethacrylate, 1,4-butanediol diacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, propoxylated neopentyl glycol diacrylate, ethylene phthalate diacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, tricyclodecyl dimethanol diacrylate, dipropylene glycol diacrylate, dimethylolpropane tetraacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate.
[0173] In certain embodiments, the acrylate is neopentyl glycol diacrylate and / or dipentaerythritol hexaacrylate.
[0174] In certain embodiments, the acrylate is neopentyl glycol diacrylate and dipentaerythritol hexaacrylate.
[0175] In certain embodiments, the acrylate is neopentyl glycol diacrylate.
[0176] In certain embodiments, the acrylate is dipentaerythritol hexaacrylate.
[0177] In certain embodiments, the reactive copolyester is a high acid value polyester.
[0178] In certain embodiments, the reactive copolyester is a high acid value polyester having an acid value of ≥10 mgKOH / g.
[0179] In certain embodiments, the reactive copolyester is selected from one or more of APT-W1 (Suzhou Hanhai New Materials Co., Ltd.), APT-44 (Suzhou Hanhai New Materials Co., Ltd.) and APT-H1 (Suzhou Hanhai New Materials Co., Ltd.).
[0180] In certain embodiments, the reactive copolyester is APT-44 (Suzhou Hanhai New Materials Co., Ltd.).
[0181] In certain embodiments, the photoinitiator is selected from one or more of photoinitiator 184, photoinitiator 369, photoinitiator 651, initiator 819, photoinitiator 907, photoinitiator 1173, and photoinitiator TPO.
[0182] In certain embodiments, the photoinitiator is photoinitiator 184.
[0183] The present invention also provides a UV anti-viscosity tape, which comprises a base film, the UV anti-viscosity adhesive and a release film.
[0184] In certain embodiments, the thickness of the UV adhesive tape is 5 to 20 μm.
[0185] In certain embodiments, the thickness of the UV adhesive tape is 5 μm, or 6 μm, or 7 μm, or 8 μm, or 9 μm, or 10 μm, or 11 μm, or 12 μm, or 13 μm, or 14 μm, or 15 μm, or 16 μm, or 17 μm, or 18 μm, or 19 μm, or 20 μm.
[0186] In certain embodiments, the UV adhesive tape has a thickness of 10 μm.
[0187] In certain embodiments, the base film is a PET film.
[0188] The present invention also provides an application of the polyester for UV viscosity-reducing adhesive, the UV viscosity-reducing adhesive, or the UV viscosity-reducing tape in the field of industrial bonding.
[0189] Example 1: Preparation of polyester for UV viscosity-reducing adhesive using 1,2-epoxy-5-hexene
[0190] Under nitrogen protection, 161.01g terephthalic acid, 161.01g isophthalic acid, 392.04g sebacic acid, 180.48g ethylene glycol, 43.67g 1,4-butanediol, 262.03g 2-methyl-1,3-propylene glycol, 199.75g 1,2-epoxy-5-hexene, 0.14g tetrabutyl titanate and 0.14g sodium acetate were added to a 2L stainless steel reactor at the same time. The reaction pressure was set to 0.1MPa, the system temperature was maintained at 100°C for 1h, and then the temperature was raised to 230°C at a heating rate of 1°C / min. When the amount of by-products of the sample was more than 90% of the theoretical value and the acid value of the system was less than 10, the esterification reaction was terminated.
[0191] After the esterification reaction was completed, the temperature was lowered to 190° C., nitrogen was introduced for protection, 0.3 g of trimethyl phosphate was added, and then the temperature was raised to 230° C. and polycondensed until the hydroxyl value of the sample was between 80-120 mg KOH / g.
[0192] Example 2: Preparation of polyester for UV viscosity-reducing adhesive using 1,2-epoxy-7-octene
[0193] Under nitrogen protection, 204.44g terephthalic acid, 204.44g isophthalic acid, 215.81g adipic acid, 183.32g ethylene glycol, 116.34g 1,6-hexanediol, 177.45g 2-methyl-1,3-propylene glycol, 298.19g 1,2-epoxy-7-octene, 0.14g tetramethyl titanate and 0.14g zinc acetate were added to a 2L stainless steel reactor at the same time. The reaction pressure was set to 0.1MPa, the system temperature was maintained at 100°C for 1h, and then the temperature was raised to 230°C at a heating rate of 1°C / min. When the amount of by-products of the sample was more than 90% of the theoretical value and the acid value of the system was less than 10, the esterification reaction was terminated.
[0194] After the esterification reaction was completed, the temperature was lowered to 190° C., nitrogen was introduced for protection, 0.3 g of trimethyl phosphate was added, and then the temperature was raised to 230° C. and polycondensed until the hydroxyl value of the sample was between 80-120 mg KOH / g.
[0195] Example 3: Preparation of polyester for UV viscosity-reducing adhesive using 1,2-epoxy-9-decene
[0196] Under nitrogen protection, 158.91g terephthalic acid, 158.91g isophthalic acid, 139.79g adipic acid, 193.46g sebacic acid, 178.12g ethylene glycol, 172.41g 2-methyl-1,3-propylene glycol, 398.38g 1,2-epoxy-9-decene, 0.14g tetramethyl titanate and 0.14g zinc acetate were added to a 2L stainless steel reactor at the same time. The reaction pressure was set to 0.1MPa, the system temperature was maintained at 100°C for 1h, and then the temperature was raised to 230°C at a heating rate of 1°C / min. When the amount of by-products of the sample was more than 90% of the theoretical value and the acid value of the system was less than 10, the esterification reaction was terminated.
[0197] After the esterification reaction was completed, the temperature was lowered to 190° C., nitrogen was introduced for protection, 0.3 g of trimethyl phosphate was added, and then the temperature was raised to 230° C. and polycondensed until the hydroxyl value of the sample was between 80-120 mg KOH / g.
[0198] Example 4: Preparation of polyester for UV viscosity-reducing adhesive using 1,2-epoxy-4-vinylcyclohexane
[0199] Under nitrogen protection, 141.33g terephthalic acid, 141.33g isophthalic acid, 258.09g sebacic acid, 240.29g dimer acid, 158.41g ethylene glycol, 207g 2-methyl-1,3-propylene glycol, 253.54g 1,2-epoxy-4-vinylcyclohexane, 0.14g tetraethyl titanate and 0.14g zinc acetate were added to a 2L stainless steel reactor at the same time. The reaction pressure was set to 0.1MPa, the system temperature was maintained at 100°C for 1h, and then the temperature was raised to 230°C at a heating rate of 1°C / min. When the amount of by-products of the sample was more than 90% of the theoretical value and the acid value of the system was less than 10, the esterification reaction was terminated.
[0200] After the esterification reaction was completed, the temperature was lowered to 190° C., nitrogen was introduced for protection, 0.3 g of trimethyl phosphate was added, and then the temperature was raised to 230° C. and polycondensed until the hydroxyl value of the sample was between 80-120 mg KOH / g.
[0201] Example 5: Preparation of polyester for UV viscosity-reducing adhesive using 4-vinylbenzyl glycidyl ether
[0202] Under nitrogen protection, 118.21g terephthalic acid, 118.21g isophthalic acid, 143.91g sebacic acid, 401.97g dimer acid, 132.50g ethylene glycol, 160.31g 2-methyl-1,3-propanediol, 324.88g 4-vinylbenzyl glycidyl ether, 0.14g tetraethyl titanate and 0.14g zinc acetate were added to a 2L stainless steel reactor at the same time. The reaction pressure was set to 0.1MPa, the system temperature was maintained at 100°C for 1h, and then the temperature was raised to 230°C at a heating rate of 1°C / min. When the amount of by-products of the sample was more than 90% of the theoretical value and the acid value of the system was less than 10, the esterification reaction was terminated.
[0203] After the esterification reaction was completed, the temperature was lowered to 190° C., nitrogen was introduced for protection, 0.3 g of trimethyl phosphate was added, and then the temperature was raised to 230° C. and polycondensed until the hydroxyl value of the sample was between 80-120 mg KOH / g.
[0204] Comparative Example 1: Preparation of Polyester for UV Viscosity Reducing Adhesive Using GMA
[0205] Under nitrogen protection, 154.29g terephthalic acid, 154.29g isophthalic acid, 375.66g sebacic acid, 172.94g ethylene glycol, 41.85g 1,4-butanediol, 251.09g 2-methyl-1,3-propanediol, 249.99g glycidyl acrylate, 0.14g tetrabutyl titanate and 0.14g sodium acetate were added to a 2L stainless steel reactor at the same time. The reaction pressure was set to 0.1MPa, the system temperature was maintained at 100°C for 1h, and then the temperature was raised to 230°C at a heating rate of 1°C / min. When the amount of by-products of the sample was more than 90% of the theoretical value and the acid value of the system was less than 10, the esterification reaction was terminated.
[0206] After the esterification reaction was completed, the temperature was lowered to 190° C., nitrogen was introduced for protection, 0.3 g of trimethyl phosphate was added, and then the temperature was raised to 230° C. and polycondensed until the hydroxyl value of the sample was between 80-120 mg KOH / g.
[0207] Comparative Example 2: Preparation of Polyester for UV Viscosity Reduction Adhesive Using MA
[0208] Under nitrogen protection, 161.03g terephthalic acid, 161.03g isophthalic acid, 392.09g sebacic acid, 180.50g ethylene glycol, 43.68g 1,4-butanediol, 262.06g 2-methyl-1,3-propylene glycol, 199.61g 1,2-epoxy-5-hexene maleic anhydride, 0.14g tetrabutyl titanate and 0.14g sodium acetate were added to a 2L stainless steel reactor at the same time. The reaction pressure was set to 0.1MPa, the system temperature was maintained at 100°C for 1h, and then the temperature was raised to 230°C at a heating rate of 1°C / min. When the amount of by-products of the sample was more than 90% of the theoretical value and the acid value of the system was less than 10, the esterification reaction was terminated.
[0209] After the esterification reaction was completed, the temperature was lowered to 190° C., nitrogen was introduced for protection, 0.3 g of trimethyl phosphate was added, and then the temperature was raised to 230° C. and polycondensed until the hydroxyl value of the sample was between 80-120 mg KOH / g.
[0210] Comparative Example 3: Preparation of Polyester for UV Viscosity Reduction Adhesive Using ITA
[0211] Under nitrogen protection, 153.86g terephthalic acid, 153.86g isophthalic acid, 374.64g sebacic acid, 172.46g ethylene glycol, 41.73g 1,4-butanediol, 250.40g 2-methyl-1,3-propanediol, 253.04g itaconic acid, 0.14g tetrabutyl titanate and 0.14g sodium acetate were added to a 2L stainless steel reactor at the same time. The reaction pressure was set to 0.1MPa, the system temperature was maintained at 100°C for 1h, and then the temperature was raised to 230°C at a heating rate of 1°C / min. When the amount of by-products of the sample was more than 90% of the theoretical value and the acid value of the system was less than 10, the esterification reaction was terminated.
[0212] After the esterification reaction was completed, the temperature was lowered to 190° C., nitrogen was introduced for protection, 0.3 g of trimethyl phosphate was added, and then the temperature was raised to 230° C. and polycondensed until the hydroxyl value of the sample was between 80-120 mg KOH / g.
[0213] Comparative Example 4: Polyester for UV viscosity-reducing adhesive with 1,2-epoxy-5-hexene content less than 50%
[0214] Under nitrogen protection, 162.67g terephthalic acid, 162.67g isophthalic acid, 396.08g sebacic acid, 182.33g ethylene glycol, 44.12g 1,4-butanediol, 264.73g 2-methyl-1,3-propylene glycol, 187.39g 1,2-epoxy-5-hexene, 0.14g tetrabutyl titanate and 0.14g sodium acetate were added to a 2L stainless steel reactor at the same time. The reaction pressure was set to 0.1MPa, the system temperature was maintained at 100°C for 1h, and then the temperature was raised to 230°C at a heating rate of 1°C / min. When the amount of by-products of the sample was more than 90% of the theoretical value and the acid value of the system was less than 10, the esterification reaction was terminated.
[0215] After the esterification reaction was completed, the temperature was lowered to 190° C., nitrogen was introduced for protection, 0.3 g of trimethyl phosphate was added, and then the temperature was raised to 230° C. and polycondensed until the hydroxyl value of the sample was between 80-120 mg KOH / g.
[0216] Comparative Example 5: Polyester for UV adhesive with 1,2-epoxy-5-hexene content higher than 70%
[0217] Under nitrogen protection, 153.21g terephthalic acid, 153.21g isophthalic acid, 373.03g sebacic acid, 171.13g ethylene glycol, 41.55g 1,4-butanediol, 249.33g 2-methyl-1,3-propylene glycol, 257.94g 1,2-epoxy-5-hexene, 0.14g tetrabutyl titanate and 0.14g sodium acetate were added to a 2L stainless steel reactor at the same time. The reaction pressure was set to 0.1MPa, the system temperature was maintained at 100°C for 1h, and then the temperature was raised to 230°C at a heating rate of 1°C / min. When the amount of by-products of the sample was more than 90% of the theoretical value and the acid value of the system was less than 10, the esterification reaction was terminated.
[0218] After the esterification reaction was completed, the temperature was lowered to 190° C., nitrogen was introduced for protection, 0.3 g of trimethyl phosphate was added, and then the temperature was raised to 230° C. and polycondensed until the hydroxyl value of the sample was between 80-120 mg KOH / g.
[0219] Example 6: Performance test of polyester for UV viscosity-reducing adhesive
[0220] The molecular weight, acid value and hydroxyl value of the polyesters prepared in Examples 1-5 and Comparative Examples 2-5 were tested. The results are shown in Table 1.
[0221] The molecular weight test was performed by Waters e2695 gel chromatography, the detector was 2414RI Detector, the chromatographic column was Styragel HR 35 μm 7.8*300 mm (THF) column, and the mobile phase was chloroform.
[0222] AV (acid value): GB / T 12008.5-2010 Plastic polyether polyols Part 5_Determination of acid value.
[0223] OHV (hydroxyl value): GB / T 12008.3-2009 Plastic polyether polyols Part 3 - Determination of hydroxyl value.
[0224] Table 1: Basic indicators of polyester for UV viscosity-reducing adhesive
[0225]
[0226] Example 7: Preparation of UV viscosity-reducing adhesive
[0227] In a 250ml three-necked flask, 150g of the polyester prepared in the above Examples 1-5 and Comparative Examples 2-5 were added respectively, and the water was removed by vacuuming at 120°C for 1h. After cooling to 80°C, a certain amount of isophorone diisocyanate was added to keep the NCO / OH ratio of the system at 1.30, and the reaction was maintained at 80°C until the NCO value was less than 3%. 1,4-butanediol was added dropwise in batches several times to continue the reaction until the NCO content was less than 0.01%, thereby obtaining a polyurethane resin.
[0228] Under a yellow light atmosphere, take 40 parts (by mass) of the above-mentioned polyurethane resin, add 30 parts of neopentyl glycol diacrylate, 15 parts of dipentaerythritol hexaacrylate, and 20 parts of reactive copolyester APT-44 (Suzhou Hanhai New Materials Co., Ltd.), and mix them at room temperature for 2 hours in a container with a stirring device until the sample is completely mixed. Then, 3 parts of photoinitiator 184 are added to the above-mentioned solution and stirring is continued at room temperature for 1 hour to obtain a UV viscosity-reducing adhesive.
[0229] The UV viscosity-reducing adhesive was coated onto 50-micron PET, baked at 150°C for 30 seconds, and then covered with a release film to block light. The dry film thickness was 10±2 μm to obtain a test tape.
[0230] Example 8: UV viscosity-reducing adhesive performance test
[0231] The UV viscosity-reducing adhesive prepared in Example 7 was subjected to a flexibility test and an adhesive strength test, and the presence of residual adhesive after the UV viscosity-reducing adhesive was evaluated. The results are shown in Table 2.
[0232] Flexibility test: Tested using a cylindrical bending instrument, referring to the standard GB / T 6742-2007 Paint and varnish bending test (cylindrical axis). At room temperature, the sample was coated on tinplate for UV curing, and three sets of experiments were performed. The cylindrical axis was 5mm, and the adhesive layer was observed to see if it was damaged. If damaged, it failed, and if intact, it passed.
[0233] Test of the adhesion of UV-resistant adhesive before illumination: Refer to the national standard GB / T2792-2014 test method for peel strength of adhesive tape, select a glass slide as the substrate to be attached, and place the adhesive on the glass slide in a constant temperature and humidity room for 2 minutes for testing at a test speed of 300mm / min.
[0234] Lighting conditions: UV adhesive is light-cured using a UV curing machine with a main wavelength of 365nm and a UV radiation intensity of 170mW / cm 2 , UV radiation energy 1000mJ / cm 2 After curing, conduct an adhesion test and observe whether there is any residual glue on the substrate.
[0235] Table 2: UV viscosity-reducing adhesive performance test results
[0236]
[0237]
[0238] The results show that the UV viscosity-reducing adhesives of Examples 1 to 5 have high initial adhesion, and the force value decreases significantly after UV irradiation. At the same time, they have high toughness, and there is no residual adhesive on the substrate. The UV viscosity-reducing adhesive of Comparative Example 1 has ester bonds in its structure, which is easy to hydrolyze and alcoholyze, resulting in a wide molecular weight distribution of its structure and poor initial adhesion before irradiation. The UV viscosity-reducing adhesive of Comparative Example 5 has a large amount of slight crosslinking during the sample synthesis process due to the excessive addition of the carbon-carbon double bond structure, resulting in poor initial adhesion before irradiation.
[0239] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A polyester for UV viscosity-reducing adhesive, characterized in that: The raw materials for preparing the polyester for UV viscosity-reducing adhesive include dibasic acid, diol, and unsaturated monomer, and the unsaturated monomer is selected from one or more of 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, 1,2-epoxy-4-vinylcyclohexane, and 4-vinylbenzyl glycidyl ether.
2. The polyester for UV viscosity reducing adhesive according to claim 1, characterized in that: The dibasic acid includes terephthalic acid, isophthalic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid, and dimer acid. Preferably, the dibasic acid is selected from one or more of terephthalic acid, isophthalic acid, adipic acid, sebacic acid, and dimer acid. Preferably, the diol includes ethylene glycol, propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, pentanediol, 1,6-hexanediol, heptanediol, octanediol, nonanediol, decanediol, polyethylene glycol, more preferably, the diol is selected from one or more of ethylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,6-hexanediol.
3. The polyester for UV viscosity reducing adhesive according to claim 2, characterized in that: In terms of molar ratio, the amount of the unsaturated monomer is 50% to 70% of the amount of the dibasic acid; Preferably, the amount of the unsaturated monomer is 30% to 60% of the amount of the diol in terms of molar ratio.
4. The polyester for UV viscosity reducing adhesive according to claim 2, characterized in that: The hydroxyl value of the polyester for UV viscosity-reducing adhesive is 80 to 120 mg KOH / g; Preferably, the hydroxyl value of the polyester for UV viscosity-reducing adhesive is 90-100 mg KOH / g.
5. The polyester for UV viscosity reducing adhesive according to claim 2, characterized in that: The raw materials for preparing the polyester for UV viscosity-reducing adhesive also include a catalyst; Preferably, the catalyst is selected from one or more of tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, sodium acetate, zinc acetate, and magnesium acetate; More preferably, the catalyst is tetrabutyl titanate and / or sodium acetate.
6. A method for preparing polyester for UV viscosity-reducing adhesive according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) Under the protection of inert gas, the raw material is kept warm and then programmed to increase the temperature to carry out an esterification reaction; (2) When the amount of by-products is greater than 90% of the theoretical value, the esterification reaction is terminated; (3) After cooling, adding a heat stabilizer under the protection of an inert gas, heating and polycondensing to obtain the polyester for UV viscosity-reducing adhesive.
7. The preparation method according to claim 6, characterized in that: The inert gas in step (1) is nitrogen; Preferably, the temperature of the insulation in step (1) is 100° C. to 120° C., and more preferably, the temperature of the insulation in step (1) is 100° C.; Preferably, the insulation time in step (1) is 40 to 80 minutes, and more preferably, the insulation time in step (1) is 60 minutes; Preferably, the programmed temperature increase in step (1) is to increase the temperature to 220°C to 240°C, and more preferably, the programmed temperature increase in step (1) is to increase the temperature to 230°C; Preferably, the rate of the programmed temperature increase in step (1) is 0.5 to 2°C / min, more preferably, the rate of the programmed temperature increase in step (1) is 1°C / min; Preferably, the cooling in step (3) is to 180°C to 200°C, and more preferably, the cooling in step (3) is to 190°C; Preferably, the inert gas in step (3) is nitrogen; Preferably, the heat stabilizer in step (3) is selected from one or more of dimethyl phosphate, trimethyl phosphate, triphenyl phosphate, and triphenyl phosphite. More preferably, the heat stabilizer in step (3) is trimethyl phosphate. Preferably, the temperature in step (3) is raised to 200°C to 240°C, and more preferably, the temperature in step (3) is raised to 230°C; Preferably, the polycondensation in step (3) is performed until the hydroxyl value of the product is 80 to 120 mg KOH / g.
8. A UV viscosity-reducing adhesive, characterized in that: The raw material for preparing the UV viscosity-reducing adhesive comprises the polyester for UV viscosity-reducing adhesive according to any one of claims 1 to 5; Preferably, the raw materials for preparing the UV viscosity-reducing adhesive further include diisocyanate, diol, acrylate, reactive copolyester and photoinitiator.
9. A UV anti-adhesive tape, characterized in that: The UV anti-viscosity tape comprises a base film, the UV anti-viscosity adhesive according to claim 8, and a release film; Preferably, the thickness of the UV adhesive tape is 5 to 20 μm, more preferably, the thickness of the UV adhesive tape is 10 μm; Preferably, the base film is a PET film.
10. Use of the polyester for UV viscosity-reducing adhesive according to any one of claims 1 to 5, or the UV viscosity-reducing adhesive according to claim 8, or the UV viscosity-reducing tape according to claim 9 in the field of industrial bonding.
Citation Information
Patent Citations
UV viscosity-reducing adhesive and preparation method thereof
CN113698908A
Polyurethane type UV viscosity-reducing adhesive and preparation method thereof
CN113736420A